ANALISIS POLA ASUH ORANG TUA DALAM PEMBALAJARAN E-LEARNING PADA MASA PANDEMI COVID- 19. - Munir, Zainal; Nisa', Anis Khoirun (Jurnal Keperawatan Profesional, 2022)
Corovirus diasease 19 or covid-19 is an epidemic that infects almost the whole world which results in changes in human life both in the economic sector, the world’s wheel of life to the realm of education. And students so that the right parenting style is needed to make student learning successfull by e-learning during the covid-19 pandemic. Goal: The study is to find out parenting styles applied to children in e-learning learning during the covid-19 pandemic. Methods: Database search includes google scholar, and science direct with the keywords parenting, e-learning, covid-19. The criteria for the selected articles are published 2020-2021 with full indonesian text with a qualitative research design. This literature review uses 10 articles that meet the inclusion and exclusion criteria. Results: Analysis of 10 articles on appropriate parenting can have a big influence on the success of e-learning during the covid-19 pandemic. Conclusion: That during the covid-19 pandemic, good parenting will result in positive child development in e-learning at home.